Enhancing Students’ Motivation and Autonomy to Learn Online and Overcome Covid 19 Outbreak - SAHLI , Fatiha (Journal of Human Sciences, 2020)
The present study aims at motivating Algerian university students and fostering their autonomy to use e learning effectively to overcome Covid 19 outbreak. In this regard, three hypotheses were specified: First, it is hypothesised that if students have an inner motivation and a willingness to study they will surely succeed to overcome this pandemic situation and study in these bad and stressful conditions. Second, if students use different academic websites effectively, it would activate and promote their autonomy to learn beyond the classroom. Third, it has also been hypothesised that if English language learners develop a certain degree of autonomy, it would lead to e learning quality improvement. To verify such a premise, a questionnaire was sent to fifty teachers of English at University Constantine 1 to collect their point of view. The results show that students who are intrinsically motivated develop their autonomy and become effective successful e learner.